Nicolas Malebranche : freedom in an occasionalist world - Peppers-Bates, Susan (Continuum studies in philosophy., 2009)
Nicolas Malebranche (1638-1715) was one of the most notorious and pious of Rene Descartes' philosophical followers. A member of The Oratory, a Roman Catholic order founded in 1611 to increase devotion to the Church and St. Augustine, Malebranche brought together his Cartesianism and his Augustinianism in a rigorous theological-philosophical system. Malebranche's occasionalist metaphysics asserts that God alone possesses true causal power. He asserts that human understanding is totally passive and relies on God for both sensory and intellectual perceptions. Critics have wondered what exactly his.